India's Arctic Policy - Building a Partnership for Sustainable Development (Ministry of Earth Sciences, 2022)
The Arctic is commonly understood to refer to region above the Arctic Circle, north of latitude 66° 34' N, which includes the Arctic Ocean with the North Pole at its centre. Eight Arctic States - Canada, Kingdom of Denmark, Finland, Iceland, Norway, Russia, Sweden and USA form the Arctic Council. The Arctic is home to almost four million inhabitants, of which approximately one-tenth are considered as indigenous people.